P606 Oh MG! the symptoms of mycoplasma genitalium in women. (14th July 2019) - Latimer, Rosie; Vodstrcil, Lenka; Read, Tim; Doyle, Michelle; Fairley, Christopher; Murray, Gerald; Bodiyabadu, Kaveesha; Kaiser, Marti; Danielewski, Jennifer; Mokany, Elisa; Tan, Litty; Chow, Eric; et al.
Abstract : Background: While the contribution of Mycoplasma genitalium (MG) to symptoms in men is well described, less is known about its clinical presentation in women. Data support an association with cervicitis, but an association with pelvic inflammatory disease is contentious. We undertook a study of 1200 symptomatic and asymptomatic women to determine the prevalence of MG and macrolide resistance, and to determine its association with common genital symptoms in women to inform indications for testing. Methods: Women attending Melbourne Sexual Health Centre from 18th April 2017 (in progress) were tested for MG and macrolide resistance (ResistancePlusMG SpeeDx, Sydney), chlamydia and gonorrhoea (Aptima Combo 2, Hologic), trichomonasis (microscopy and culture), bacterial vaginosis (BV) and candida (microscopy). Women underwent examination and completed a questionnaire on symptoms. The prevalence of MG, macrolide-resistance, STIs and coinfection, and association with genital symptoms and signs, was determined by univariate and multivariable analysis. Results: Of 1054 women enrolled to date (968 symptomatic and 86 asymptomatic), 62 women (6%, 95%CI 5–7%) tested positive for MG, with macrolide-resistance detected in 54% (95%CI 41–67%). Chlamydia and gonorrhoea were detected in 8% (95%CI 6–9%) and 1% (95%CI 1–2%) of the 1054 women respectively. Of the 62 women infected with MG, 42% (95%CI 30–55) also had BV, 26% (95%CI 16–38) candida, 6% (95%CI 2–16) chlamydia and 2% (95%CI 0–9) gonorrhoea. MG prevalence did not differ between symptomatic and asymptomatic women (6% vs 5%, p=0.614). No specific genital symptoms or signs were significantly associated with MG, in contrast to chlamydia, which was associated with post-coital bleeding (OR 1.7, p=0.04) and cervicitis (OR 2.3, p=0.014). Conclusion: MG was as common as chlamydia in our clinic population but in contrast to chlamydia was not associated with any specific clinical features that would inform testing practices. Macrolide resistance was detected in half of cases and coinfection with BV was particularly common. Disclosure: No significant relationships.